Odontogenic cysts: A 40- year retrospective clinicopathological study in an Iranian population - Narges Ghazi; Nasrollah Saghravanian; Reza Zare-mahmoodabadi; Saleh Hosseinpour (Cumhuriyet University, 2015)
We present a 40-year retrospective study of 1189 patients with odontogenic cysts (OCs) that were diagnosed from 1971 to 2011 in the Department of Oral and Maxillofacial Pathology, Faculty of Dentistry, Mashhad, Iran. In contrast to most of previous studies that have been reported inflammatory OCs as the most common type, in the current study, among cystic lesions of the jaws most were developmental in origin (62.30%). The most commonly diagnosed inflammatory and developmental odontogenic cysts were the periapical cyst (30.45%) and dentigerous cyst (26.80%) respectively. Developmental cysts were happened more in males whereas inflammatory types showed more tendency to females. The patients' mean age was 27.20 ± 15.93 years, with a peak of occurrence in the second decade of life followed by the third decade. A high posterior mandibular incidence (41.85%) was observed, whereas some previous reports showed anterior maxilla predilection. The most common histological types of developmental cysts were aggressive (Dentigerous cyst, odontogenic keratocyst and calcifying odontogenic cyst). Furthermore, these three varieties representing more than half of all studied cysts (59.30%) at our Service. Knowledge of the incidence of odontogenic cysts and their clinicopathologic features, including most common location, gender and age distribution in different ethno-geographic backgrounds is necessary for the accurate diagnosis and differentiating aggressive lesions from other kinds of cysts .